Digital-Based Photoelectric Effect Practicum Toolkit: Curriculum and Student Analysis - Dewi Hikmah Marisda; Ana Dhiqfaini Sultan; Syamsuriana Basri; Irma Sakti Tahir; Nurjannah Nurjannah (Jurnal Penelitian Pendidikan IPA, 2023)
Physics education study programs at several private universities in South Sulawesi are still limited in implementing Modern Physics practicum. The implementation of Modern Physics practicum at College A is limited to three practicum units, while College B has never held a Modern Physics practicum. This is because college B does not yet have a modern physics laboratory and practicum unit. Therefore, researchers developed modern physics practical tools. The Modern Physics practicum device is designed using Arduino Uno which is equipped with a digital practicum module. The aim of this research is to describe the stages of definition in aspects of curriculum analysis, beginning and end, and student needs. This research is research and development using the 4D-Thiagarajan model. Research data was analyzed descriptively. The results of the research show that one of the important Modern Physics practicum contents according to course achievements is the Photoelectric Effect. It is hoped that the development of the Photoelectric Effects practicum equipment can become a learning medium for students and a precursor to the development of other Modern Physics practicum units at the two universities